Pengaruh Fitur Keamanan, Kemudahan Penggunaan Dan Kualitas Pelayanan Terhadap Kepuasan Pengguna Aplikasi Dana - Syaffa Aulia Andyani; Tiara Turay (GLOBAL SCIENTS PUBLISHER, 2025)
This research aims to determine the effect of security features, ease of use and service quality on DANA application user satisfaction (case study of Bachelor of Management students at Dharma Andalas University, Padang). The population in this study was 518 undergraduate management students at Dharma Andalas University, Padang, with samples taken using the Raosoft sample size calculator so that the sample was 110 respondents. Data was obtained by distributing questionnaires and then processed and tested using IBM SPSS Statistics 22. From the research carried out, it is known that based on the results of hypothesis testing, it shows 1). Security features have a positive and significant effect on user satisfaction, 2). Convenience has a positive and significant effect on user satisfaction, 3). Service quality has a positive and significant effect on user satisfaction, 4). Security features, ease of use and service quality have a positive and significant effect on user satisfaction. Furthermore, the user satisfaction variable is influenced by security features, ease of use and service quality by 73.8%, namely the remaining 26.2% is influenced by other variables that are not in this study.